2020
DOI: 10.21037/tcr.2019.12.11
|View full text |Cite|
|
Sign up to set email alerts
|

Matrine reverses the drug resistance of K562/ADM cells to ADM and VCR via promoting autophagy

Abstract: Background: This study aimed to investigate the effects of matrine (MAT) on the drug resistance of K562/ ADM cells.Methods: K562/S and K562/ADM cells were treated with different concentrations of vincristine (VCR), adriamycin (ADM), and/or MAT for 48 h. The cell viability was determined by MTT assay, and the drugresistant multiple and drug-resistant reversal multiple were calculated based on half-inhibitory concentration (IC50). The cell apoptosis, as well as cell cycle were detected by flow cytometry. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Consistent with this view from the studies by Li et al [ 88 ] and Takahashi et al [ 89 ] reported that cotylenin A, which is a plant-growth regulator, in combination with vincristine, synergistically inhibited the growth of myeloma cells and induced apoptosis. Interestingly Cotylenin A with vincristine synergistically induced autophagy, as evidenced by LC3-II accumulation and p62/SQSTM1 degradation.…”
Section: Direct Involvement Of Microtubules In Autophagysupporting
confidence: 60%
See 2 more Smart Citations
“…Consistent with this view from the studies by Li et al [ 88 ] and Takahashi et al [ 89 ] reported that cotylenin A, which is a plant-growth regulator, in combination with vincristine, synergistically inhibited the growth of myeloma cells and induced apoptosis. Interestingly Cotylenin A with vincristine synergistically induced autophagy, as evidenced by LC3-II accumulation and p62/SQSTM1 degradation.…”
Section: Direct Involvement Of Microtubules In Autophagysupporting
confidence: 60%
“…Li et al [ 88 ] studied the effects of Matrine (MAT) in the K562/ADM cell line. MAT is an alkaloid that sensitizes K562/ADM cells to Adriamycin and vincristine, and at the same time, promotes autophagy, as evidenced by autophagic vacuole accumulation, increased LC3 punctate fluorescence, increased LC3 II protein levels, and p62/SQSTM1 protein degradation.…”
Section: Direct Involvement Of Microtubules In Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Matrine is an active component of the botanical drug Sophora flavescens, which exhibits potent anti-tumor properties. Matrine targets ATGs and affects the cell cycle of tumor cells, enhancing the sensitivity of drug-resistant cells to vincristine (VCR) and adriamycin (ADM) [ 88 ].…”
Section: Natural Products Overcome Autophagy-mediated Tumor Drug Resi...mentioning
confidence: 99%
“…The NPs andrographolide [ 59 ], α-hederin [ 62 ], jolkinolide B [ 63 ], PC3-15 [ 64 ], pristimerin [ 65 ], icariin [ 67 ], apigenin [ 69 ], tea polyphenol [ 70 ], genistein [ 71 ], phloretin [ 72 ], FMNT [ 73 ], rutin [ 74 ], berberine [ 86 , 87 ], matrine [ 88 ], ursolic acid [ 104 ], betulinic acid [ 90 ], triptolide [ 92 ], oleanolic acid [ 93 ], AGE [ 94 ], demethylzeylasteral [ 95 ], resveratrol [ 96 ], piceatannol [ 98 ], quercetin [ 99 ], hyperoside [ 100 ], scutellarin [ 101 ], chrysin [ 102 ], thymoquinone [ 103 ], tetrandrine [ 126 , 127 ], lycorine [ 134 ], carnosic acid [ 137 ], β-elemene [ 140 ], curcumin [ 141 ], luteolin [ 155 ], and epigallocatechin gallate [ 145 ] are associated with autophagy in tumor cells. These NPs can control autophagy in tumor cells such as those of the liver, pancreatic, gastric, breast, myeloma, lung, glioma, colorectal, ovarian, cervical, and oral malignancies, and thus combat drug resistance.…”
Section: Natural Products Overcome Autophagy-mediated Tumor Drug Resi...mentioning
confidence: 99%